A Study on the Power Parameter in Power Prior Bayesian Analysis. Issue 1 (2nd January 2023) - Han, Zifei; Ye, Keying; Wang, Min
Abstract: The power prior and its variations have been proven to be a useful class of informative priors in Bayesian inference due to their flexibility in incorporating the historical information by raising the likelihood of the historical data to a fractional power δ . The derivation of the marginal likelihood based on the original power prior, and its variation, the normalized power prior, introduces a scaling factor C ( δ ) in the form of a prior predictive distribution with powered likelihood. In this article, we show that the scaling factor might be infinite for some positive δ with conventionally used initial priors, which would change the admissible set of the power parameter. This result seems to have been almost completely ignored in the literature. We then illustrate that such a phenomenon may jeopardize the posterior inference under the power priors when the initial prior of the model parameters is improper. The main findings of this article suggest that special attention should be paid when the suggested level of borrowing is close to 0, while the actual optimum might be below the suggested value. We use a normal linear model as an example for illustrative purposes.